Structural Analysis of Pylon Head for Cable Stayed Bridge Using Non-Linear Finite Element Method - Akbar, Musthafa; Nugraha, Aditya Sukma (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2018)
Cable-stayed bridge is a type of bridge structure that commonly used for long-span range. This study provides an important opportunity to advance the understanding nonlinearities of material and geometry which is used for pylon of cable-stayed bridge structure. This study limited to response of pylon structure subjected to tension load which already calculated previously using structural analysis program. The methodology of structural analysis in order to determine working stress in the pylon structure under cable tension load is based on non-linear finite element method by incorporating an elastic-plastic material model and involve large deformation logarithm. In this study, laboratory experiment was held using test method ASTM A370. In finite element of plasticity analysis Ramberg-Osgood model was used to generate stress-strain curve of material. Based on finite element analysis that we have done, both of pylon structure will be fail or experience permanent plastic deformation if it subjected to loading conditions as mentioned in this research. The most critical regions in the structure are at Section A2 for left side pylon and at Section A11 for right side pylon. In critical regions, maximum Von-Misses stress reach 427.96 MPa for left side pylon and 430.56 MPa for right side pylon. Those stress value are beyond yield strength of material which is used for the structure. Design optimization can be done for the structure with some considerations, e.g. modification of design in the critical region, improve material properties or just change thickness of material in the critical regions.